2020
DOI: 10.22441/mix.2020.v10i3.008
|View full text |Cite
|
Sign up to set email alerts
|

How Work Satisfaction and Organization Climate Influence Organizational Citizenship Behaviour

Abstract: The research explores the influence of job satisfaction and organizational climate on organizational citizenship behavior. The object of this research are employees at PT.CCM. The research conducted to 60 respondents by delivering a questionnaire. The data analysis conducted with multiple linear regression tests. The result of this research shows that there is a partially and simultaneously correlation between job satisfaction and organizational climate toward organizational citizenship behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This explains that academic staff of private universities would often show high level of tolerance as long as they engage in collaborative works. Many past studies reported related findings (Almaqableh, et al, 2021;Fahim and Asadollahi, 2021;Harmius, et al, 2021;Nugroho, et al, 2020;Nabilla and Riyanto, 2020). For instance, research established that teamwork climate had a positive significant influence on organizational citizenship behaviour across industries and cultures.…”
Section: Test Of Hypothesesmentioning
confidence: 87%
See 4 more Smart Citations
“…This explains that academic staff of private universities would often show high level of tolerance as long as they engage in collaborative works. Many past studies reported related findings (Almaqableh, et al, 2021;Fahim and Asadollahi, 2021;Harmius, et al, 2021;Nugroho, et al, 2020;Nabilla and Riyanto, 2020). For instance, research established that teamwork climate had a positive significant influence on organizational citizenship behaviour across industries and cultures.…”
Section: Test Of Hypothesesmentioning
confidence: 87%
“…He describes it as a shared perception of what an organization is like. Therefore, it is the individual perception toward a particular condition that shows the internal environment quality of the organization towards what they see and what they feel, and what the member of the organization thought (Nugroho, et al, 2020).…”
Section: Organizational Climatementioning
confidence: 99%
See 3 more Smart Citations